Optimizing Temperature and Oxygen Supports Long-term Culture of Human Islets. Issue 2 (February 2019) - Komatsu, Hirotake; Rawson, Jeffrey; Medrano, Leonard; Cook, Colin A.; Barriga, Alyssa; Gonzalez, Nelson; Salgado, Mayra; Omori, Keiko; Kandeel, Fouad; Tai, Yu-Chong; Mullen, Yoko
Background: Islet transplantation is a promising treatment for type-1 diabetes; however, donor shortage is a concern. Even when a pancreas is available, low islet yield limits the success of transplantation. Islet culture enables pooling of multiple low-yield isolations into an effective islet mass, but isolated islets rapidly deteriorate under conventional culture conditions. Oxygen (O2 ) depletion in the islet core, which leads to central necrosis and volume loss, is one of the major reasons for this deterioration. Methods: To promote long-term culture of human islets in PIM-R medium (used for islet research), we adjusted temperature (12°C, 22°C, and 37°C) and O2 concentration (21% and 50%). We simulated the O2 distribution in islets based on islet O2 consumption rate and dissolved O2 in the medium. We determined the optimal conditions for O2 distribution and volume maintenance in a 2-week culture and assessed viability and insulin secretion compared to noncultured islets. In vivo islet engraftment was assessed by transplantation into diabetic nonobese diabetic-severe combined immunodeficiency mouse kidneys. We validated our results using CMRL 1066 medium (used for clinical islet transplantation). Results: Simulation revealed that 12°C of 50% O2 PIM-R culture supplied O2 effectively into the islet core. This condition maintained islet volume at greater than 90% for 2 weeks. There were no significant differences in viability and function in vitro or diabetic reversal rate in vivo between 2-week cultured and noncultured islets. Similar results were obtained using CMRL 1066. Conclusions: By optimizing temperature and O2 concentration, we cultured human islets for 2 weeks with minimal loss of volume and function. Abstract : Culture of pancreatic islets pooled from multiple low-yield isolations could allow an effective islet mass, but islets rapidly deteriorate due to oxygen depletion in the islet core. Culture of islets in 12°C–50% oxygen maintain islet volume at >90% for 2 weeks with no significant differences in diabetic reversal rate in vivo compared with noncultured islets. Supplemental digital content is available in the text.